Characterization of the complete chloroplast genome of Sargassum fusiforme and its phylogenomic position within phaeophyceae. Issue 2 (3rd July 2019) - Zhang, Yonghua; Wang, Shengqin; Qian, Weiguo; Shi, Yijian; Li, Nan; Yan, Xiufeng; Zou, Huixi; Wu, Mingjiang
Abstract: Sargassum fusiforme is an important economic seaweed in East Asia. In this study, we characterized the complete chloroplast genome sequence of S. fusiforme using PacBio long-read sequencing technology. It had a circular mapping molecular with the length of 124, 286 bp, with a large single-copy region (LSC, 73, 437 bp) and a small single copy region (SSC, 40, 131 bp) separated by a pair of inverted repeats (IRs, 5, 359 bp). The cp genome contained 173 genes including 139 protein-coding, 6 rRNA, and 28 tRNA genes. The phylogenomic analysis indicated that S. fusiforme is closely related to S. thunbergii .